2016
DOI: 10.3844/ajessp.2016.282.290
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Dioxide Utilization for an Enhanced Biohydrogen Production of a Biomass Hydrolysate

Abstract: Bio-hydrogen (H 2 ) production in a thermophilic anaerobic bioreactor with carbon dioxide (CO 2 ) utilization at the headspace was investigated at different ratio of Biomass substrate to Microorganism (B/M). A 3 mL volume of 80% NaOH (m/v) solution was continuously hung at the headspace of the bioreactors to capture carbon dioxide. The utilization of CO 2 at its headspace, proved to enhance bio H 2 production. The highest Cumulative Biohydrogen Yield (CHY) of 131.81±3.47 mL-H 2 /gVS was measured at the ratio o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…In most cases, carbon dioxide's by‐productivity had no apparent relation with biohythane production. However, a study by Abug and Oh (2016) found that the presence of carbon dioxide inside the bioreactors improved the performance of the hydrogen production process. Therefore, cumulative carbon dioxide side production is also depicted in Exhibit 3 to observe whether carbon dioxide significantly impacts biohydrogen production.…”
Section: Resultsmentioning
confidence: 99%
“…In most cases, carbon dioxide's by‐productivity had no apparent relation with biohythane production. However, a study by Abug and Oh (2016) found that the presence of carbon dioxide inside the bioreactors improved the performance of the hydrogen production process. Therefore, cumulative carbon dioxide side production is also depicted in Exhibit 3 to observe whether carbon dioxide significantly impacts biohydrogen production.…”
Section: Resultsmentioning
confidence: 99%